2021
DOI: 10.1111/jmft.12501
|View full text |Cite
|
Sign up to set email alerts
|

Couple teletherapy in the era of COVID‐19: Experiences and recommendations

Abstract: The unprecedented times of the novel Coronavirus quarantine and subsequent stay‐at‐home orders have changed the way many couple therapists provide clinical services. Understanding couple therapists’ experiences with teletherapy is important for optimizing future telehealth delivery with couples. Thus, the purpose of this mixed methods survey study was to explore couple therapists’ experiences of transitioning from in‐person/traditional therapy to online/telehealth delivery. A total of 58 couple therapists comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
73
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(86 citation statements)
references
References 24 publications
0
73
0
Order By: Relevance
“…(13,47,51,52,(57)(58)(59) Patients feels more at ease when they are surrounded by the environment they are used to and family and their loved pets. (39,46,51,52) This feature was emphasized in mental health related studies. Patients tended to be more open, felt more secure and often shared more with their therapists during the online sessions from their homes.…”
Section: Bene Ts Of Remote Workmentioning
confidence: 99%
See 4 more Smart Citations
“…(13,47,51,52,(57)(58)(59) Patients feels more at ease when they are surrounded by the environment they are used to and family and their loved pets. (39,46,51,52) This feature was emphasized in mental health related studies. Patients tended to be more open, felt more secure and often shared more with their therapists during the online sessions from their homes.…”
Section: Bene Ts Of Remote Workmentioning
confidence: 99%
“…(48,51) Some physicians reported that it was easier to consult patients via digital care visits because their cases were simpler than those in physical visits, which in turn allowed to treat them more quickly, e ciently as well as consult more patients. (37,39) Satisfaction Overall, healthcare professionals, regardless of their specialization or location, had mostly positive experience with digital care visits ranging from at least slightly (46) to highly satis ed (35,40,44) as stated in nearly half of the selected publications. Professionals felt that digital care visits have a positive in uence on their work environment, (13) were generally happy with their experience, (41,43,(51)(52)(53) and enjoyed it.…”
Section: Bene Ts Of Remote Workmentioning
confidence: 99%
See 3 more Smart Citations